2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33272
|View full text |Cite
|
Sign up to set email alerts
|

Smartness in Engineering Culture: An Interdisciplinary Dialogue

Abstract: Ohio State University. She holds a B.S. in Mechanical Engineering (Kansas State '08), a M.S. in Industrial Engineering (Purdue '14) and a Ph.D. in Engineering Education (Purdue '15). Her team, Beliefs in Engineering Research Group (BERG) utilizes qualitative methods to explore beliefs in engineering. Her research has an overarching goal of leveraging engineering education research to shift the culture of engineering to be more realistic and inclusive. Dr. Dringenberg is also interested in neuroscience, growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This contribution is warranted because while some have revealed the reinforcing ways that everyday moments in engineering result in the sorting of students as capable of doing engineering or not (Secules et al, 2018), many other engineering education researchers' efforts to directly investigate the idea of ability (including our own) have mostly focused on intelligence through the lens of Dweck's mindset theory (Dringenberg et al, 2018; Dringenberg & Kramer, 2019; Reid & Ferguson, 2014; Stump et al, 2014), and more work is needed to understand how smartness as a cultural practice manifests in engineering education. Furthermore, we focus on shared beliefs because we understand them as a pragmatic way to connect individual and cultural levels of educational practice (Dringenberg et al, 2019).…”
Section: Research Purpose and Questionsmentioning
confidence: 99%
“…This contribution is warranted because while some have revealed the reinforcing ways that everyday moments in engineering result in the sorting of students as capable of doing engineering or not (Secules et al, 2018), many other engineering education researchers' efforts to directly investigate the idea of ability (including our own) have mostly focused on intelligence through the lens of Dweck's mindset theory (Dringenberg et al, 2018; Dringenberg & Kramer, 2019; Reid & Ferguson, 2014; Stump et al, 2014), and more work is needed to understand how smartness as a cultural practice manifests in engineering education. Furthermore, we focus on shared beliefs because we understand them as a pragmatic way to connect individual and cultural levels of educational practice (Dringenberg et al, 2019).…”
Section: Research Purpose and Questionsmentioning
confidence: 99%
“…Recent attention to smartness in engineering culture (Dringenberg et al, 2019) and our participants' rejection of this stereotype suggests that this might be an interesting area for future research.…”
Section: Discussionmentioning
confidence: 91%
“…The excerpt from the focus group showed how students resist the notion of smartness but collectively maintained a narrative of engineers' superior status. Departing from the broader public narrative of smartness (i.e., as represented on "the internet"; see Dringenberg et al, 2019;Kramer et al, 2020) they identified hard work and the conceptual nature of engineering as markers of the discipline's superiority. In a striking pattern of shared speech, the students collectively negotiated a consensus around these alternative definitional markers in ways that included nuance ("everyone can do it") and also demarcated engineering from other, "lesser" disciplines ("She [a nursing major] had to memorize everything.…”
Section: Discussionmentioning
confidence: 99%